STUDY OF BALINESE CUSTOMARY LAW ON INHERITANCE RIGHTS OF CHILDREN FROM INTERFAITH MARRIAGES - Ketut Sudiatmaka; I G A Lokita Purnamika Utami; Ni Ketut Sari Adnyani; I Wayan Landrawan (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This study aims to determine (1) the study of Balinese customary law on the inheritance rights of children born from interfaith marriages; (2) the status of the heirs of children born from interfaith marriages; and (3) legal consequences for the heirs of children born from interfaith marriages (a case study in the village of Alatgker, District of Buleleng, District of Buleleng). This type of research is an empirical juridical research with a basic research scheme, using a method with a statutory approach and a conceptual approach. sources of primary and secondary legal materials. Legal material collection techniques are carried out by: document studies, field observations (observations), and interviews. The research location is in the village of… using a qualitative descriptive analysis of legal materials. The results of the study show that interfaith marriages in the Marriage Law in Indonesia are not explicitly regulated in the Marriage Law Number 1 of 1974 concerning Juncto Marriage, Law Number 16 of 2019 concerning amendments to the Marriage Law Number 1 of 1974 concerning Marriage. The Marriage Law requires couples of different religions if they want to marry, they must submit to the religion of one of the parties. As for the inheritance rights of children born from marriages of couples of different religions according to Balinese customary law, if the child follows his father's religion, he will be given the right to inherit. However, if the child follows the religion of his mother, he will not get the right to inherit. This is based on that the Balinese customary inheritance law adheres to the limeusa principle (father line) and inheritance is not only in the form of rights but also certain obligations that can only be carried out by heirs of the same religion as the heir.